Evaluation of clinical trials of ethnomedicine used for the treatment of diabetes: A systematic review - Elmi, Gul Rehman; Anum, Kamil; Saleem, Kalsoom; Fareed, Rameesha; Noreen, Sobia; Wei, Haiyan; Chen, Yongxing; Chakraborty, Avirup; Rehman, Masood Ur; Liyuan, Shi; Abbas, Muhammad; Duan, Yongtao (Frontiers in Pharmacology, 2023)
Diabetes mellites (DM) is most widespread metabolic disorder with yearly 6.7 million deaths worldwide. Currently, effective chemical drugs are available but their toxicity including weight gain, hepatotoxicity, nephrotoxicity, and risk of cardiovascular illnesses is of great concern. Thus, traditional ethnomedicine for DM have gained great interest by researchers that work via prevention of glucose intestinal absorption and hepatic production, enhancing glucose absorption into muscle and fat tissues and increasing insulin secretion. Large number of plants have entered clinical trials with some being approved for use. Current study provides evaluation of such clinical trials for which extensive literature review was performed by searching keywords in databases including “ethnomedicine diabetes clinical trial”, “clinical trials”, “clinical trial in diabetes”, “diabetes”, “natural products in diabetes”, “ethno-pharmacological relevance of natural products in diabetes”, etc. Based on eligibility criteria, clinical trials of 20 plants and natural products were found and evaluated. Major limitations of clinical trials were lack of patient compliance, dose-response relationship and biomarkers evaluation with small sample size and treatment duration. Various measures in terms of more strict regulations can be considered to achieve quality clinical trials. Specific goal of this systematic review is to discuss DM treatment through ethnomedicine based on recent clinical trials of previous seven years.